PROSEDUR PENGUJIAN SUBTANTIF AKUN ASURANSI DIBAYAR DI MUKA PADA PT. Z OLEH KANTOR AKUNTAN PUBLIK HERTANTO, GRACE, KARUNAWAN - Muja Putra Rachmansyah (2023)
Examination Procedures Audit of Prepaid Expenses accounts is a series in the audit process that cannot be forgotten. This procedure is carried out to check the correctness of the balance of prepaid expenses in the financial statements. The prepaid fee audit procedure is a series of activities carried out by KAP HGK for PT. Z which is engaged in manufacturing. The purpose of writing this final report is to explain data related to prepaid insurance at PT. Z and to understand the audit procedures for PT. Z prepaid insurance accounts By KAP HGK. Writing is done using a descriptive analysis method in which the author has explained several steps and findings from observations when the writer carried out field work practices. The results obtained show that KAP HGK has carried out audit procedures in accordance with auditing standards in Indonesia. PT. Z has also recorded correctly and is able to show evidence in the form of a contract or policy which shows that this amount can be charged to each period of the insurance period even though there was an error in recording the value of PT. Z prepaid insurance but KAP HGK has made adjustments.